"REGIONAL INDUSTRIAL DEVELOPMENT (CASE STUDY OF NAVOI REGION)" - Murtazayev Isabek Bazarbayevich (Innovate Conferences, 2025)
Navoi Region, located in the central part of the Zarafshan area, is distinguished by its vast mineral resource potential and highly industrialized economy. Key minerals include gold, uranium, silver, rare metals, phosphorite, asbestos, feldspar, marble, and other precious stones, with the Muruntov gold mine ranking among the world’s largest. Navoi city functions as a multifunctional regional center, while Zarafshan, Uchkuduk, and Gazgan are specialized industrial towns, and Kiziltepa and Yangirabot serve as agro-industrial district centers. In 2024, 26.0% of the employed population worked in the industrial sector, reflecting the region’s strong industrial orientation. Industry and construction together account for 71.9% of the regional economy, making Navoi the most industrialized region in Uzbekistan. The region plays a leading role nationally in metallurgy (47.3%), electric power (16.3%), chemical and petrochemical industries (11.3%), construction materials (9.2%), and machine-building (5.6%). Between 2010 and 2024, metallurgical production nearly doubled, while other industrial sectors declined, indicating increasing specialization in metallurgy. The region’s industrial output, major enterprises, and sectoral structure demonstrate its strategic economic importance and highlight trends in regional industrial development.
Keywords: Navoi Region, industrial development, mineral resources, metallurgy, economic specialization, sectoral structure, regional economy, mining industry, industrial output, economic growth.